Kinematics and Dynamics Analysis of Lower Limb Robot based on Human Motion Data - Hailong Du; Ningning Hu (Jixie chuandong)
For patients with lower limb dyskinesia，the combination of robotic systems and biomedical systems has brought good news to patients. The analysis of human gait law through medical perspective can better develop and drive robotic systems. Therefore， based on the idea of importing human motion data as a reference trajectory into the robot system，the human lower limb motion data and plantar force data are collected experimentally through 3D infrared motion capture system and 3D force measuring platform system. The algorithm is used to filter and fit the collected data. By establishing the link model of the lower limb exoskeleton robot，the rotation angle and torque curve of the hip joint and knee joint are deduced and calculated based on experiment data based on experim ent data，an adaptive controller is designed based on Matlab，and effectiveness of kinematics and dynamics analysis based on experimental data is verified，which provides data support and theoretical basis for the motor selection and control system design of the lower limb exoskeleton robot.